Primary malignant mesenchymoma of bone (Medical Journal of Indonesia, 2001)
Pimary malignant mesenchymoma of bone (PMMB) is an exceedingly rare neoplasm consisting of two or more unrelated malignant mesenchymal components other than fibrosarcoma or malignant fibrous histiocytoma. Review of the literature reports only 16 cases, most of which were composed of osteosarcoma and liposarcoma. We report a case af PMMB composed of liposarcoma, rhabdomyosarcoma and high grade chondrosarcoma arising within the left distal femur in a 52-year-old male, resulting in the patient's death 3 months after presentation. (Med J Indones 2001;10: 235-41)